The Influence of Product Attributes, Price, and Image on Customer Loyalty - Erika Nurmartiani (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the influence of product attributes, price, and brand image on customer loyalty at Sundanese restaurants in Bandung City. The study was conducted in 2024 with a quantitative approach, making Sundanese restaurant customers the focus of observation. Primary data were collected through a 5-point Likert scale-based questionnaire with a simple random sampling technique from 200 respondents. The analysis was carried out using the Structural Equation Modeling (SEM) method with LISREL software. The results showed that product attributes and price did not have a significant effect on customer loyalty. On the contrary, brand image plays an important role in shaping loyalty, with brand reputation as the main factor. These findings indicate that in the context of Sundanese restaurants, customer perceptions of brand image, especially reputation, determine loyalty more than product quality or price. This study enriches the marketing literature related to the role of brand image and provides guidance for Sundanese restaurant managers to prioritize strengthening brand reputation in order to increase customer loyalty amidst the competition in the culinary industry. Further research can explore other factors such as service quality to deepen understanding of customer loyalty.